Никитич: (Леонид Борисович Красин) : [1870-1926] / Б. Л. Могилевский - Могилевский Борис Львович (Госполитиздат, 1963)
Экземпляры: КХ (20250317) / Инвентарный номер: 0130262 / Сис.шифр: 3КП1(092) / Авт.знак: М 74 / ГРНТИ: 11 / ББК: 66